The Determinants of Tariff and Nontariff Trade Restrictions in the United States - Ray, Edward John (Journal of Political Economy, 1981)
This paper develops and tests a simple model for the determination of tariff and nontariff barriers to trade across industries within the United States, using 1970 trade data. We find that nontariff trade restrictions have supplemented tariff protection in the United States. Both tariff and nontariff trade restrictions are biased toward industries in which the United States has an apparent comparative disadvantage in world trade and away from industries in which consumer welfare losses from protection would be great. We also find substantial evidence that tariff and nontariff trade restrictions predominate in industries with very different market characteristics.